Dynamic change of serum levels of some branched amino acids and tryptophan in athletic horse after different physical exercise - Arfuso, F.; Assenza, A.; Fazio, F.; Rizzo, M.; Giannetto, C.; Piccione, G. (Journal of Equine Veterinary Science, 2019)
Physical exercise induces several adaptations involving modulation of the energetic pathways to meet the energy demand during physical exercise. The branched-chain amino acids (BCAAs), and leucine in particular, are considered as the most relevant amino acids, especially for exercise physiology. In this study the change of leucine, valine and tryptophan concentration was investigated in athletic horse before and after different exercise type. A total of 40 sport horses were equally dived in 4 groups according to exercise type: group A (jumping), group B (reining), group C (32-km ride), group D (72-km ride). Blood samples were collected before (TPRE), immediately after (TPOST) and 30 minutes after (TPOST30) the race to assess leucine, valine, and tryptophan concentration. Two-way ANOVA showed an effect of time and/or exercise on the serum leucine, valine and tryptophan values in all groups (P < 0.01). Lower leucine and valine values were found in groups A, B and D at TPOST and TPOST30 respect to TPRE, whereas group C showed higher values at TPOST and TPOST30 compared to the values found at TPRE. All groups showed increased tryptophan values at TPOST and TPOST30 compared to TPRE. Lower leucine, valine and tryptophan values were found in group D at TPOST30 compared to the values found at TPOST. These dynamic changes suggest the involvement of amino acid metabolism during different exercise types. These findings are probably related to the complex physiological adaptations to exercise stressor that allow re-establishment of the homeostatic equilibrium of the organism.